2018
DOI: 10.1108/nfs-10-2017-0205
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions towards a healthy diet among a sample of university people in Portugal

Abstract: 22Purpose: A healthy diet has been recognized as one of the most important factors associated with the 23 maintenance of human health as well as to help preventing the development of some chronic 24 diseases. Therefore, this work aimed at studying the perceptions of a sample of university people 25 regarding a healthy diet. Author version2 Methodology: It was undertaken a descriptive cross-sectional study on a non-probabilistic sample of 27 382 participants. The data was collected among a sample of Portuguese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 88 publications
(94 reference statements)
2
12
2
Order By: Relevance
“…Significant differences were found by country and level of education, with adult citizens residing in Portugal and those with higher education showing a more correct perception of what healthy eating should be. These results are in line with those of the study by Ferrão et al [ 30 ]. They are also consistent with the results of Lê et al [ 34 ] who showed an association between a high educational level and adherence to a healthy diet.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Significant differences were found by country and level of education, with adult citizens residing in Portugal and those with higher education showing a more correct perception of what healthy eating should be. These results are in line with those of the study by Ferrão et al [ 30 ]. They are also consistent with the results of Lê et al [ 34 ] who showed an association between a high educational level and adherence to a healthy diet.…”
Section: Discussionsupporting
confidence: 94%
“…The questionnaire used in this study was first validated for the Portuguese population [ 28 , 29 , 30 ] and then applied in other countries, after translation and adaptation. The questionnaire was applied in Brazil in Portuguese and translated into Spanish, following a back-translation methodology for validation.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have focused on the relation between nutrition knowledge and people's dietary patterns, and some of them highlighted that there might be a positive correlation between higher nutrition knowledge and the adoption of healthier diets. Nevertheless, other works were not so decisive about this association (Rustad and Smith 2013;Spronk et al 2014;Ferrão et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…There are relatively few studies showing a relationship between BMI and the perception of diet, i.e., concern about nutrition. It is known, however, that the healthy diet perception score may decrease with increasing BMI [ 50 ]. Higher diet quality may attenuate genetic predisposition to obesity, and therefore people with a lower BMI may perceive a healthy diet differently than those with a higher BMI [ 51 ].…”
Section: Discussionmentioning
confidence: 99%